PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIK SISWA SMP MELALUI METODE PENEMUAN TERBIMBING BERBANTUAN 1 SOFTWARE GEOGEBRA DI SMP N 25 PEKANBARU - ., Annajmi (Edu Research, 2016)
This research aims to know 1) the increase in the ability of mathematical representations of students through guided discovery methods GeoGebra software assisted and guided discovery method without software GeoGebra, 2) the interactionbetween the learning and early mathematical ability of students on increase students' ability of mathematical representations. This study is a quasi-experimental research. The instruments used are mathematical representations ability tests. The data obtained was analyzed using analysis of covariance with SPSS. Based on the analysis concluded that 1) the increased ability of mathematical representations of students through guided discovery learning methods GeoGebra software assisted higher than the increase in the ability of mathematical representations of students through guided discovery learning method without software GeoGebra. There is no interaction between the learning and early mathematical ability of students on increase students'ability of mathematical representations. Students activity in learning by using guided discovery method with software Geogebra was better than students activity without Geogebra software.